2012
DOI: 10.4321/s1137-66272012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced acute esophageal lesions and use of ciprofloxacin

Abstract: ResuMenPresentamos el caso de una mujer de 95 años con lesiones agudas del esófago que tomaba ciprofloxacino por cistitis aguda. La paciente refería dolor y sensación de cuerpo estraño retroesternal asociados con hematemesis y melena, después del segundo día de tratamiento. No había antecedentes personales de trastornos gástricos o esofágicos. La endoscopia digestiva objetivó lesiones sangrantes en el tercio medio del esófago. El uso de ciprofloxacino fue suspendido y se utilizó un inhibidor de la bomba de pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…of 2 days to 2 months. 43 The symptoms of patients with DIE improved within a week in most patients and up to 4 weeks in others, while the mucosal recovery took a median of 3 weeks and can be as long as 1 year. Toya et al found that the use of PPIs may not be sufficient to prevent DIE by retrospective analysis.…”
Section: Original Researchmentioning
confidence: 93%
“…of 2 days to 2 months. 43 The symptoms of patients with DIE improved within a week in most patients and up to 4 weeks in others, while the mucosal recovery took a median of 3 weeks and can be as long as 1 year. Toya et al found that the use of PPIs may not be sufficient to prevent DIE by retrospective analysis.…”
Section: Original Researchmentioning
confidence: 93%